2019
DOI: 10.1038/s41419-019-1593-2
|View full text |Cite
|
Sign up to set email alerts
|

Beta1 integrin blockade overcomes doxorubicin resistance in human T-cell acute lymphoblastic leukemia

Abstract: Growing evidence indicates that cell adhesion to extracellular matrix (ECM) plays an important role in cancer chemoresistance. Leukemic T cells express several adhesion receptors of the β1 integrin subfamily with which they interact with ECM. However, the role of β1 integrins in chemoresistance of T-cell acute lymphoblastic leukemia (T-ALL) is still ill defined. In this study, we demonstrate that interactions of human T-ALL cell lines and primary blasts with three-dimensional matrices including Matrigel and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 50 publications
0
28
0
Order By: Relevance
“…Also consistent with inside-out signaling, we detect talin-1 activation in CD82OE treated with daunorubicin. Additionally, the restored chemosensitivity of CD82OE cells following treatment with the α4β1 inhibitor is supported by recent findings in T-Acute Lymphoblastic Leukemia where blockade of β1 integrin sensitized xenografted leukemic cells to doxorubicin and diminished leukemic burden in the bone marrow ( 62 ). Collectively, our work supports a previously proposed concept where a tetraspanin-PKC-integrin complex is essential for signaling ( 63 ) and goes on to suggest that the level of CD82 expression serves as a modulator of signal intensity and perhaps signal duration critical for chemoresistance.…”
Section: Discussionmentioning
confidence: 59%
“…Also consistent with inside-out signaling, we detect talin-1 activation in CD82OE treated with daunorubicin. Additionally, the restored chemosensitivity of CD82OE cells following treatment with the α4β1 inhibitor is supported by recent findings in T-Acute Lymphoblastic Leukemia where blockade of β1 integrin sensitized xenografted leukemic cells to doxorubicin and diminished leukemic burden in the bone marrow ( 62 ). Collectively, our work supports a previously proposed concept where a tetraspanin-PKC-integrin complex is essential for signaling ( 63 ) and goes on to suggest that the level of CD82 expression serves as a modulator of signal intensity and perhaps signal duration critical for chemoresistance.…”
Section: Discussionmentioning
confidence: 59%
“…Interestingly, α2β1 integrin but not fibronectin-binding integrins is among the adhesion molecules identified. In addition, we recently reported that the blockade of β1 integrin overcomes doxorubicin resistance in a model of T-ALL xenograft 40 . While additional studies are needed to sort out the role of each α integrin subunit in leukemia chemoresistance, our findings argue for an important role for the collagen-binding integrin α2β1 in the chemoresistance of both AML and T-ALL.…”
Section: Discussionmentioning
confidence: 99%
“…In the collagen-rich microenvironment, the activation of integrin β1 and its downstream effector JNK mediated resistance to sorafenib in triple-negative breast cancer ( Nguyen et al., 2014 ). In addition, resistance to Adriamycin in patients with T-cell acute lymphoblastic leukemia might be due to the interaction between integrin β1 and matrigel that activated the ABCC1 drug transporter ( Berrazouane et al., 2019 ). Glucocorticoid drugs are often used to reduce the toxic and side effects of chemotherapeutic drugs ( Chen et al., 2010 ).…”
Section: Integrins and Cancer Drug Resistancementioning
confidence: 99%